Preliminary study on genetic distance of Vibrio parahaemolyticus isolates from diseased fish and shrimp brackishwater ponds by random amplified polymorphic DNA (RAPD) in Malaysia - Musa, Najiah; Lee, K. L.; Mohd Daud, Hassan; Mohamed Din, Mohamed Shariff; Mohd Lila, Mohd Azmi (Asian Fisheries Society, 2003)
This study was conducted to determine the genetic distance of V. parahaemolyticus isolates from diseased fish (clinical) and shrimp brackishwater ponds (environmental) in Malaysia;four clinical isolates (numbered F1 to F4) and six environmental isolates (W1 to W6) from shrimp brackishwater ponds. The isolates were identified using conventional biochemical tests in combination with BBL Crystal Kit TM. Two published 10-mer arbitrary primers (Gen1-50-01 and Gen1-50-02) were used for detecting DNA polymorphisms. RAPDistance program (version 1.04) was used to analyze the RAPD patterns. Dendrogram was then constructed from the combined results of two primers using Neighbour-Joining Tree (NJTREE) algorithm. The primers detected DNA polymorphisms in all isolates except W1 and W2, which were DNA monomorphic. Each primer generated fingerprints of up to 20 bands, ranging from 100 to 6000 bp. Dendrogram elucidated a tree of two main clusters (A and B) where a close genetic distance between the clinical isolates (F2, F3 and F4) except isolate F1 was observed to be closer to environmental isolates W3 and W5. Isolates W1, W2 and W4 were found to be genetically far from any clinical isolates.